Wacana Sastera Transendental : The discourse of transcendental literature - Musa, Mohd Faizal (Jurnal Pengajian Media Malaysia, 2011)
One of the main discourses in Islamic Literature in Indonesia is Transcendental Literature as proposed by Kuntowijoyo. This essay is to review his thoughts on the essence of Transcendental Literature. In doing so, his original ideas were compared to aspects of Sufism and Structuralism. According to Kuntowijoyo, transcendental principles are put forward and applied in literary works by using symbolism. Interpretation of the meaning of the symbols is part of the enjoyment in reading these “transcendental works”. Kuntowijoyo also encouraged creative elements, which in Indonesian language are called “inklusivisme” (inclusion of foreign elements in literary works). By discussing and revealing the background, pillars, themes, criterions and Transcendental Literature”s application in literary works, the uniqueness of Islamic Literature in Indonesia can be perceived by practitioners and academics. Salah satu wacana utama dalam Kesusasteraan Islam di Indonesia adalah Sastera Transendental seperti yang dikemukakan oleh Kuntowijoyo. Esei ini adalah untuk mengulas pemikirannya mengenai intipati Sastera Transendental. Dengan melakukannya, idea asalnya dibandingkan dengan aspek tasawuf dan strukturalisme. Menurut Kuntowijoyo, prinsip transendental dikemukakan dan diterapkan dalam karya sastera dengan menggunakan simbolisme. Tafsiran makna simbol adalah sebahagian daripada keseronokan dalam membaca "karya transendental" ini. Kuntowijoyo juga mendorong elemen kreatif, yang dalam bahasa Indonesia disebut "inklusivisme" (masuknya unsur asing dalam karya sastera). Dengan membahas dan mengungkapkan latar belakang, tiang, tema, kriteria dan penerapan Sastera Transendental dalam karya sastera, keunikan Sastera Islam di Indonesia dapat dirasakan oleh para praktisi dan akademik.